2007
DOI: 10.1016/j.bbrc.2007.05.114
|View full text |Cite
|
Sign up to set email alerts
|

The isolated polycystin-1 COOH-terminal can activate or block polycystin-1 signaling

Abstract: Much of what is known of the activities of polycystin-1 has been inferred from the effects of the isolated cytoplasmic COOH terminal domain, but it is not clear whether the truncation acts like polycystin-1, as a dominant negative, or in unrelated pathways. To address this question, we have examined functional interactions between the intact and truncated forms of polycystin-1 in one cell system. In cells expressing only native polycystin-1, introduction of the truncation replicated the activity of the full-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It has been suggested that effects of the cleaved PC1 tail may be due to a dominant-negative effect on endogenous, full-length PC1 (16). To test this possibility, we used Pkd1-null mouse embryonic fibroblasts (MEFs).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that effects of the cleaved PC1 tail may be due to a dominant-negative effect on endogenous, full-length PC1 (16). To test this possibility, we used Pkd1-null mouse embryonic fibroblasts (MEFs).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a number of studies using the C-terminal tail of PC1 over expressed as a fusion protein have found the inverse; the expression of C-terminal tail leads to increases in intracellular Ca 2+ and SOCE [32], [33]. However, in light of recent findings by Basavanna et al (2007)[34] who showed that the over expression of a PC1 C-terminus fusion protein acted as a dominant negative, these seemingly contrary findings may in fact be supportive of our hypothesis that PC1 expression leads to inhibition of the SOCE.…”
Section: Discussionmentioning
confidence: 97%
“…Studying PC1 cleavage has been complicated by the fact that there are at least two different C-terminal fragments that can be released by cleavage (Chauvet et al ., 2004; Low et al ., 2006). Expressing a soluble form of the C-terminal fragment could yield information about the effects of these peptides on intracellular signaling pathways, but this gives no insight into the processes that generate the soluble peptides and may actually produce results that are difficult to interpret in a physiological context (Basavanna et al ., 2007). The endogenous fragments produced by these cleavage events within the full-length protein are often short-lived and found in low abundance.…”
Section: Assay Rationale and Historymentioning
confidence: 99%